English for Vocational Education: Developing Interactive English Materials with Quizizz for Office Management and Business Services Students of SMKN 1 Mataram - Nurhaliza, Baiq Intan; Sujana, I Made; Apgrianto, Kurniawan; Melani, Boniesta Zulandha; Munandar, La Ode Alfin Haris (Journal of English Education Forum (JEEF), 2025)
This study explores the development of English learning materials using Quizizz-based interactive design for tenth-grade students of Office Management and Business Services (OMBS) at SMKN 1 Mataram. Vocational high schools aim to equip students with both specialized skills and essential competencies, such as English, which is taught as a foreign language tailored to meet the specific needs of the OMBS curriculum. The integration of technology, particularly through the use of Quizizz, enhances the learning experience by promoting engagement and motivation among students. The study employs the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) for material development, ensuring alignment with student needs and curricular goals. Expert validation and student-teacher feedback reveal that the materials are highly effective, with students demonstrating increased motivation and improved learning outcomes. The interactive elements of Quizizz, including polls, open-ended questions, and various quiz formats, foster an engaging and interactive learning environment. The findings suggest that Quizizz-based learning materials can significantly enhance the learning process, making it more enjoyable and effective for vocational high school students. This research serves as a reference for future studies on material development and highlights the potential of Quizizz as a valuable tool for interactive education.